GEOTECHNICAL INVESTIGATIONS FOR THE FAILURE REACHES OF THE MAIN CANAL OF SUBARNAREKHA IRRIGATION PROJECT - Dr. R. Chitra; Dr. Manish Gupta; Shahid Noor (International Journal of Innovations in Engineering Research and Technology, 2021)
The Subarnarekha multipurpose river valley project is an interstate project which will benefit Jharkhand, Odisha and West Bengal. Subarnarekha main canal is the life line of the interstate Subarnarekha irrigation project serving as the main water conductor that feeds the command area reservoirs for distribution and catering to its own command. The Subarnarekha mail canal in Odisha state is 46.5 km long. The construction of the canal stretches are almost complete bu in operational due to some geological problem. A particular reach of Subarnarekha main canal of 770 m long has been giving problems and has held back the scheme completion and consequently realization of envisaged benefits